Large carnivore expansion in Europe is associated with human population density and land cover changes. Issue 4 (18th January 2021) - Cimatti, Marta; Ranc, Nathan; Benítez‐López, Ana; Maiorano, Luigi; Boitani, Luigi; Cagnacci, Francesca; Čengić, Mirza; Ciucci, Paolo; Huijbregts, Mark A. J.; Krofel, Miha; López‐Bao, José Vicente; Selva, Nuria; et al.
Abstract: Aim: The recent recovery of large carnivores in Europe has been explained as resulting from a decrease in human persecution driven by widespread rural land abandonment, paralleled by forest cover increase and the consequent increase in availability of shelter and prey. We investigated whether land cover and human population density changes are related to the relative probability of occurrence of three European large carnivores: the grey wolf ( Canis lupus ), the Eurasian lynx ( Lynx lynx ) and the brown bear ( Ursus arctos ). Location: Europe, west of 64° longitude. Methods: We fitted multi‐temporal species distribution models using >50, 000 occurrence points with time series of land cover, landscape configuration, protected areas, hunting regulations and human population density covering a 24‐year period (1992–2015). Within the temporal window considered, we then predicted changes in habitat suitability for large carnivores throughout Europe. Results: Between 1992 and 2015, the habitat suitability for the three species increased in Eastern Europe, the Balkans, North‐West Iberian Peninsula and Northern Scandinavia, but showed mixed trends in Western and Southern Europe. These trends were primarily associated with increases in forest cover and decreases in human population density, and, additionally, with decreases in the cover of mosaics of cropland and natural vegetation. Main conclusions: Recent land cover and human population changes appear to have altered the habitat suitability pattern for large carnivores in Europe, whereas protection level did not play a role. While projected changes largely match the observed recovery of large carnivore populations, we found mismatches with the recent expansion of wolves in Central and Southern Europe, where factors not included in our models may have played a dominant role. This suggests that large carnivores' co‐existence with humans in European landscapes is not limited by habitat availability, but other factors such as favourable human tolerance and policy.